2021
DOI: 10.1177/17590914211005074
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Models to Analyze the Glioma Microenvironment

Abstract: Animal models are still indispensable for understanding the basic principles of glioma development and invasion. Preclinical approaches aim to analyze the treatment efficacy of new drugs before translation into clinical trials is possible. Various animal disease models are available, but not every approach is useful for addressing specific questions. In recent years, it has become increasingly evident that the tumor microenvironment plays a key role in the nature of glioma. In addition to providing an overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…By contrast, patient-derived orthotopic xenografts (PDOXs) are created by implanting tumor tissue or cells from a patient into a mouse in the same anatomic location in order to further emulate the tumor microenvironment. The major disadvantages of rodent models are the differences in physiological parameters compared with humans, the lower complexity of the tumor microenvironment, and the rapid clearance of drugs from the body due to fast liver metabolism [32][33][34][35][36]. In addition to that, they are also time-consuming and expensive to develop and cannot be shared among scientists, and perhaps most significantly, they require immunocompromised animals for developing patient-derived xenograft models [37,38].…”
Section: In Vivo Models For Pediatric Cancersmentioning
confidence: 99%
“…By contrast, patient-derived orthotopic xenografts (PDOXs) are created by implanting tumor tissue or cells from a patient into a mouse in the same anatomic location in order to further emulate the tumor microenvironment. The major disadvantages of rodent models are the differences in physiological parameters compared with humans, the lower complexity of the tumor microenvironment, and the rapid clearance of drugs from the body due to fast liver metabolism [32][33][34][35][36]. In addition to that, they are also time-consuming and expensive to develop and cannot be shared among scientists, and perhaps most significantly, they require immunocompromised animals for developing patient-derived xenograft models [37,38].…”
Section: In Vivo Models For Pediatric Cancersmentioning
confidence: 99%
“…CAR T cells can be significantly modified using contemporary genetic technologies like CRISPR/Cas9 in order to increase their therapeutic efficacy, persistence, and safety. Majority of glioma models employ immunosuppressed mice, which do not accurately replicate the tumor microenvironment to detect CAR T cell responses [ 191 ]. For the effective development of manipulation tactics, a deeper comprehension of the CNS environment in which CAR T cells function is important.…”
Section: Perspectives and Critical Analysesmentioning
confidence: 99%
“…Another major limitation includes the time the tissue is obtained (at diagnosis, surgical resection or post-mortem), as it has been shown that molecular features and response to therapies differ depending on the time of tissue collection [ 234 ], and a further significant limitation is the use of immunocompromised mice. The lack of an immune microenvironment in these models makes it impossible to study the tumour-immune microenvironment and their interactions [ 235 ]. Recently, with the advances in genome editing, the use of genetically engineered animal models has gained a lot of attraction.…”
Section: Comparison Between Zebrafish and Other Paediatric Brain Canc...mentioning
confidence: 99%